2019
DOI: 10.1111/ced.13888
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in epidermal function prevent relapse of psoriasis: a self‐controlled study

Abstract: While therapeutic approaches for psoriasis are widely available, preventive regimens are lacking. We aimed to determine whether improvements in epidermal function could prevent psoriasis relapse. Two self-controlled cohort studies were designed, enrolling two cohorts of patients with psoriasis (n = 30 and n = 60) to be treated topically with an in-house-prepared emollient or ATOPALM â cream applied twice daily to one forearm for 20 and 30 days, respectively, while the same sites on the contralateral arm served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In addition, infants with higher TEWL rates during the first week of life predict a higher risk of atopic dermatitis later in the life independently of filaggrin mutations [39]. Likewise, TEWL rates predict the relapse of psoriasis, i.e., psoriasis relapses sooner in subjects with higher TEWL rates [4]. We showed here that uninvolved skin sites of subjects with hand eczema displayed higher TEWL rates, suggesting that TEWL rates could possibly serve as a proxy in predicting the risk of developing hand eczema, a notion which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, infants with higher TEWL rates during the first week of life predict a higher risk of atopic dermatitis later in the life independently of filaggrin mutations [39]. Likewise, TEWL rates predict the relapse of psoriasis, i.e., psoriasis relapses sooner in subjects with higher TEWL rates [4]. We showed here that uninvolved skin sites of subjects with hand eczema displayed higher TEWL rates, suggesting that TEWL rates could possibly serve as a proxy in predicting the risk of developing hand eczema, a notion which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, topical applications of a barrier repair emollient in combination with topical glucocorticoid cream reduced psoriasis area severity index scores by approximately 25% in comparison to glucocorticoid cream alone [3]. Moreover, recent studies demonstrated that improvements in epidermal permeability barrier function delayed the relapse of psoriasis [4]. Furthermore, expression levels of proinflammatory cytokines in normal-appearing aged murine skin could also be lowered simply by improvements in epidermal permeability barrier function [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a key pathogenic role of defective permeability barrier in the development of atopic dermatitis and psoriasis is also well appreciated. Accordingly, improvements in epidermal permeability barrier can prevent and alleviate both atopic dermatitis and psoriasis . Pertinently, at least one clinical study demonstrated that topical Hirudoid ® cream improves atopic dermatitis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epidermal permeability barrier homeostasis, other epidermal functions, such as pH and stratum corneum hydration, also regulate cutaneous functions [19][20][21][22]. Accordingly, improvements in epidermal function could benefit multiple cutaneous and extracutaneous functions [17,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%